Impact of Climate Change on Precipitation and Temperature Changes in the Northwest Region of Bangladesh Using SDSM: A Comparison of CanESM2 and HadCM3 Models (Journal of Engineering Science, 2024)
Assessment of climate change-induced precipitation and temperature changes is crucial for the adaptive and sustainable management of water resources in a country. The objective of this study is to explore the impact of climate change on future precipitation and temperature changes in the northwest region of Bangladesh using the statistical downscaling model (SDSM). In this study, Rajshahi station is taken as the case study area, and two widely applied general circulation models (GCMs), namely the Canadian Earth System Model (CanESM2) and the Hadley Center Coupled Model (HadCM3), are used for the climate change analysis. The results demonstrate that after bias correction, the CanESM2-based downscaling model performs better compared to the HadCM3-based downscaling model. The bias-corrected models for both GCMs are then employed for the projection of future precipitation and temperatures for the 2040s and 2090s, considering climate change scenarios. The precipitation trend is found to be negative for both GCMs in all scenarios. Considering the worst climate change scenarios for both GCMs (i.e., the RCP8.5 scenario in the CanESM2 and the A2 scenario in the HadCM3), the mean annual precipitation will be decreased by 9.3% and 4.5% in the 2040s and 12.1% and 4.1% in the 2090s. Furthermore, the mean annual maximum temperature will be increased by 0.233°C and 0.245°C in the 2040s and 0.468°C and 0.633°C in the 2090s, whereas the mean annual minimum temperature will be increased by 0.394°C and 0.188°C in the 2040s and 0.394°C and 0.357°C in the 2090s. Thus, the current study comes to the conclusion that decreased precipitation and increased temperatures will have an effect on the water resources in the study region, leading to a reduction in the overall supply of surface water and groundwater storage. It is expected that the study findings will help water managers and policymakers in developing a framework for sustainable and adaptive water management in the face of climate change.Journal of Engineering Science 14(2), 2023, 127-136